Impact of Bariatric Surgery on Liver Enzymes. - Fayyadh, Firas Fadhil (International Tinnitus Journal)
Background: Bariatric surgery is superior to conservative procedures in terms of weight loss in obese people. In the long term, it can reduce the incidence of obesity by up to 40% and alleviate a myriad of associated diseases. Since obesity is the leading cause of non-alcoholic fatty liver disease, most importantly, losing weight is one of the first recommendations for individuals with NAFLD. Aim of the study: Comparison of liver function testing pre-and post-bariatric operation. Patients and methods: In Baghdad City's private al-dawlia Hospital and private Jenin Hospital divisions of surgery, a prospective research was carried out. From first of Jan 2020 to 30th of December 2022, the 100 patients with severe obesity were recruited in the trial and underwent bariatric surgery (53 patients with SG and 47 patients with bypass), and who accepted to participate in study and selected according to specific criteria. Results: The mean age was (31.69 ± 8.466 years) with 64% of females and 36% of males, the mean of pre-surgical BMI was 47kg/m2 but after 2 years the post-surgical BMI was 29kg/m2 with statically significant differences. Also, there was a decrease in all liver function tests when compared before and after surgery, with statically significant association (p=0.001). In addition to that we found the AST, ALT and TSB more decrease among SG group than bypass group. Conclusion: Bariatric surgery is effective for rapid weight loss and maintenance with contribute to prolonged decreased liver function tests.